Alimentação natural de peixes ornamentais da ordem siluriformes: uso de isótopos estáveis - Avendaño Vasquez, Leonardo [UNESP] (2015)
The production and extraction of ornamental fish for trading aquarism, remains as a fast growing sector of the aquaculture industry. As a group sensitive to environmental changes in ecosystems, they reflect high levels of anthropic variation and their preservation is imperative, not just for the reason of being part of a great variety, but also by being part of socioeconomic activity of a human population that generally lives of fishing. There is a necessity to evaluate the impact caused by humans in the environmental conservation and biodiversity in developing countries. Loricariidae family presents more than 800 species, meanly restrict in tropical countries of Center and South America spread out in four subfamilies: Ancistrinae, Hypoptopomatinae, Hypostominae and Loricariinae. Nevertheless this elevated diversity, few species are cultivated, on account of a lack of knowledge about their ecology and distribution. Therefore, knowledge about feeding habits of certain fish species is of fundamental importance when the main purposes are based on trying to conserve the environment where they are located. This study was done with the aim of identifying trophic levels of benthic species by determination of stable isotopes. This study expects to strengthen knowledge of environmental status of these species, by knowing their trophic relationships, to contribute to the optimization of nutrition and generate alternative production of ornamental fish in the country